PENGARUH CUSTOMER SERVICE STRATEGIES TERHADAP AMAZING CUSTOMER EXPERIENCES MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI - -, Muhammad Saifuddin Muntasir -; -, Sri Wahyuni -; -, Salman Alfarisy Totalia - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2016)
The aims of this research are: (1) to know the effect of the customer service strategies consisting of membership, serious fun, partnership, hire right, after-experience, community, and walk the walk toward the amazing customer experiences in students of Economic Education Study Program; (2) to know the effect of the membership toward the amazing customer experiences in students of economic education study program; (3) to know the effect of the serious fun toward the amazing customer experiences in students of Economic Education Study Program; (4) to know the effect of the partnership toward the amazing customer experiences in students of Economic Education Study Program; (5) to know the effect of the hire right toward the amazing customer experiences in students of Economic Education Study Program; (6) to know the effect of the after-experience toward the amazing customer experiences in students of Economic Education Study Program; (7) to know the effect of the community toward the amazing customer experiences in students of Economic Education Study Program; (8) to know the effect of the walk the walk toward the amazing customer experiences in students of Economic Education Study Program. The research is descriptive quantitative. The population of the research were all of students of Economic Education Study Program in 2013-2015 with the total number of 187 student. The samples of the research were 127 student by using proportionate sratified random sampling. The data were obtained by questioners. The data were analyzed by using double regression, F test and T test. The results of this research show: (1) there is an positive effect of the customer service strategies consisting of membership, serious fun, partnership, hire right, after-experience, community, and walk the walk toward the amazing customer experiences in students of Economic Education Study Program; (2) there is an positive effect of the membership toward the amazing customer experiences in students of Economic Education Study Program; (3) there is an negative effect of the serious fun toward the amazing customer experiences in students of Economic Education Study Program; (4) there is an negative effect of the partnership toward the amazing customer experiences in students of Economic Education Study Program; (5) there is an negative effect of the hire right toward the amazing customer experiences in students of Economic Education Study Program; (6) there is an positive effect of the after-experience toward the amazing customer experiences in students of Economic Education Study Program; (7) there is an positive effect of the community toward the amazing customer experiences in students of Economic Education Study; (8) there is an positive effect of the walk the walk toward the amazing customer experiences in students of Economic Education Study Program.ABSTRAK Tujuan penelitian ini adalah: (1) mengetahui pengaruh Customer service strategies yang terdiri dari Membership, Serious FUN, Partnership, Hire right, After-experience, Community, dan Walk the walk secara simultan terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (2) mengetahui pengaruh Membership terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (3) mengetahui pengaruh Serious FUN terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (4) mengetahui pengaruh Partnership terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (5) mengetahui pengaruh Hire right terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (6) mengetahui pengaruh After-experience terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (7) mengetahui pengaruh Community terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (8) mengetahui pengaruh Walk the walk terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi. Penelitian ini merupakan penelitian kuantitatif deskriptif. Populasi dalam penelitian ini adalah mahasiswa Prodi Pendidikan Ekonomi FKIP UNS Surakarta tahun 2013-2015 yang berjumlah 187 mahasiswa. Sampel dalam penelitian ini berjumlah 127 mahasiswa dengan teknik pengambilan sampel proportionate sratified random sampling. Teknik pengumpulan data menggunakan angket atau kuesioner. Teknik analisis data menggunakan regresi berganda, uji F dan uji T. Hasil penelitian ini menunjukkan: (1) terdapat pengaruh positif Customer service strategies yang terdiri dari Membership, Serious FUN, Partnership, Hire right, After-experience, Community, dan Walk the walk secara simultan terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (2) terdapat pengaruh positif Membership terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (3) terdapat pengaruh negatif Serious FUN terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (4) terdapat pengaruh negatif Partnership terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (5) terdapat pengaruh negatif Hire right terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (6) terdapat pengaruh positif After-experience terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (7) terdapat pengaruh positif Community terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi; (8) terdapat pengaruh positif Walk the walk terhadap Amazing customer experiences pada mahasiswa Prodi Pendidikan Ekonomi.